POPULATION DYNAMICS OF WHITEFLY ON POTATO PLANTED ON DIFFERENT DATES - Paul, Santanu; Konar, A. (Potato Journal, 2013)
The results of the investigation done at Hougly indicated that whitefly (Bemisia tabaci, Guen.) (i.e. 4th Des, 11th Dec and 18th Dec) appeared on the crop during early December in case of first two plantings (i.e. 20th Nov and 27th Nov.) while it was by the end of December in other plantings (i.e. 4th Dec. 11th Dec and 18th Dec.). Similarly, in first and second plantings, the highest population of this hemipteran was recorded during fourth week of December, but in case of others, it was obtained by the end of January except fifth planting where it was during first week of February under the environmental conditions of 17.8 to 20.2Â°C mean temperature and 75.2 to 77.9% mean relative humidity (R.H.) with very little rainfall. The infestation of whitefly was highest in fourth planting (25.12) followed by first (23.87), fifth (23.00), third (18.99) and second plantings (17.66), respectively. It was also observed that the pest population in different planting dates was negatively associated with mean temperature (r =-0.2240 to-0.7381) and rainfall (r =-0.2162 to-0.4328) whereas positively related with mean R.H. (r = 0.0155 to 0.6955) and in first two plantings, the population was profoundly related with climatic factors while in others, the crop age might have played an important role regarding population development of the pest. Thus, both abiotic and biotic factors are responsible for population build of whitefly on potato. Therefore, to escape high whitefly infestation, the potato crop should be planted in between last week of November and first week of December in this locality.